Fragranone C: a new dihydrochalcone glucopyranoside from Anneslea fragrans twigs - Ashraf M. Omar (2020)
© 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group. A phytochemical investigation of an ethanolic extract of Anneslea fragrans twigs collected from Thailand resulted in the discovery of a new dihydrochalcone glucopyranoside named fragranone C (1), together with six previously reported compounds. The structural elucidation of the new compound was achieved by HRFABMS, NMR spectroscopic analysis and acid hydrolysis.